Development of a New Method for Simulating Gas-to-Particle Conversion During Sodium Pool Fires in SFR Containment. (2nd October 2020) - Sun, Hongping; Deng, Jian; Zhu, Dahuan; Zhang, Yapei; Tian, Wenxi; Qiu, Suizheng; Su, G. H.
Abstract: Sodium combustion oxide aerosols are the main carriers of radioactive materials in a sodium-cooled fast reactor (SFR) during sodium fire accidents. Therefore, it is of great significance to simulate aerosol behavior in sodium pool fires to evaluate radioactive source terms in the containment or environment. In this work, a numerical method has been developed to simulate sodium oxide aerosol behavior during sodium pool fires. The Classical Nucleation Theory has been taken into account to simulate gas-to-particle conversion (GPC). The model has been evaluated theoretically in 280 cases with three main parameters: sodium pool temperature, pool diameter, and oxygen concentration. The correlation established by fitting data points is associated with the sodium evaporation rate. The SFA code has been developed based on advanced sodium pool combustion and aerosol models coupled with GPC correlations. In comparison with the experimental data, the code-calculated average atmospheric temperature, airborne aerosol concentration, and particle size are in good agreement with the data, which indicate that the method is reliable and can be applied in code development in the future.